Development of algorithm for calculation of operation and repair efficiency of a plate heat exchanger - S. M. Chekardovsky; K. N. Ilyukhin; A. A. Melekhin; M. N. Chekardovsky (Vestnik MGSU)
Introduction. The relevance of the topic is due to the determination of the efficiency of the design and operation of heat exchangers as a result of the development of digital technologies in science and technology, including after scheduled and unscheduled repairs of devices. At the present time, a lot of normative, educational and methodological documentation has been developed. The problem is insufficient reliability of determination of efficiency of heat exchangers.Materials and methods. To solve the problem, an algorithm for calculating the efficiency of operation and repair of a plate heat exchanger is developed. The authors have created algorithms and a programme in Microsoft Excel for the design calculation of the heat exchanger, including thermal, design and hydraulic calculations of the heat exchanger, as well as the calculation of exergy the designed apparatus according to the heat exchanger design calculation programme. The web application ntcseis.ru based on the Ukit programming language can be used as an implementation of the calculation of the exergy efficiency of a plate heat exchanger.Results. Design calculation of a plate heat exchanger was performed using the Microsoft Excel programme, including thermal, design and hydraulic calculations of the heat exchanger. A manual calculation of the exergy of the designed apparatus was performed as a solution to an applied problem to determine the efficiency of the designed heat exchanger. The web application ntcseis.ru of calculation of exergy efficiency of a plate heat exchanger was developed.Conclusions. In the process of the work, the following tasks were set and solved: thermal, design and hydraulic parameters of the heat exchanger were calculated on the basis of the well-known classical methodology. The calculation results were used to determine the exergy losses of the designed heat exchanger using the calculated values of the average logarithmic temperatures and other parameters of the heating and heated heat carriers; exergy losses from heat exchange with the environment, from the final temperature difference of heat carriers, from hydraulic resistances in the paths of heat carriers; specific thermal exergy of heat carriers at the inlet and outlet of the heat exchanger; exergy flow at the inlet and outlet of the apparatus; exergy coefficient of the heat exchanger. A web application ntcseis.ru of calculation of the exergy efficiency of a plate heat exchanger is developed.